2023
DOI: 10.1017/s1368980023000939
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a text-messaging intervention on intuitive eating: a randomised controlled trial

Abstract: Intuitive eating (IE) is a concept based on mind-body integration of instinct, emotion and rational thought, to improve eating behaviors, physical and mental health. Several attempts were developed to teach IE principles including text-messaging interventions given that they are easy to implement and low-cost. Objective The present study aimed to assess the effectiveness of a five-week text-message-based IE intervention on IE, while correcting for perceived stress (PS) and self-compassion (SC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Furthermore, there is evidence IE can be modified according to context and population, such as its delivery format (e.g., online delivery, facilitated workshops; Babbott et al, 2022;Manana et al, 2023) and sample (e.g., college students, partners of military members; Burnette & Mazzeo, 2020;Burnette et al, 2022;Cole & Horacek, 2010). As such, research has found self-management (i.e., the participant is responsible for implementing, measuring, and evaluating their own behaviors) to be feasible and efficacious (Babbott et al, 2022; for example, see Boucher et al, 2016).…”
Section: Intuitive Eatingmentioning
confidence: 99%
“…Furthermore, there is evidence IE can be modified according to context and population, such as its delivery format (e.g., online delivery, facilitated workshops; Babbott et al, 2022;Manana et al, 2023) and sample (e.g., college students, partners of military members; Burnette & Mazzeo, 2020;Burnette et al, 2022;Cole & Horacek, 2010). As such, research has found self-management (i.e., the participant is responsible for implementing, measuring, and evaluating their own behaviors) to be feasible and efficacious (Babbott et al, 2022; for example, see Boucher et al, 2016).…”
Section: Intuitive Eatingmentioning
confidence: 99%